Antioxidant enzymes and compounds complement each other during arsenic detoxification in shoots of Isatis cappadocica Desv. Issue 10 (25th November 2016) - Karimi, Naser; Souri, Zahra
ABSTRACT: Isatis cappadocica has been reported to be an arsenic (As) hyperaccumulator. Antioxidant enzymes and compounds have been proposed to play an important role in the detoxification and tolerance of As. In the present study, As-induced oxidative stress and antioxidant responses were investigated on I. cappadocica grown hydroponically in response to application of arsenate (0–1200 μmol). As accumulation increased with an increase in arsenate concentration in the medium. Along with a significant increase in arsenate concentration, a build up in hydrogen peroxide, indicators of oxidative stress, was observed. The activity of superoxide dismutase and peroxidase was induced after arsenate treatment, reached a maximal value at 800 μmol arsenate and then declined at the highest arsenate treatment. Glutathione reductase activity and contents of non-enzymatic antioxidants (carotenoids, flavonoids and anthocyanins) increased significantly as arsenate concentration augmented. These results indicated that high efficient antioxidant system may play significant roles in As detoxification and improve I. cappadocica tolerance against As toxicity.